AN ANALYSIS OF SLANG WORDS IN THE SONG GOD’S PLAN BY DRAKE - Asti Nur Cahyani; Siti Lutfiah; Erlita Priha; Eny Maulita Purnama Sari (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2026)
This research aims to analyze the slang words used in God’s Plan by Drake, focusing on their types, meanings, and functions within the song’s context. The study employed a qualitative descriptive method, using the lyrics as the primary data source. A total of 50 slang words were identified and categorized into 18 types of word formation. The findings reveal that 10 types appear in the song: clipping (20%), variation (16%), final combining forms (12%), compounding (12%), prefixes and suffixes (12%), blending (6%), acronyms and initialisms (6%), coinage (4%), derivation (4%), multiple processes (4%), and conversion (4%). These slang words serve to create an informal tone, convey social identity, reflect cultural and geographical context, and maintain rhythmic and stylistic flow in the lyrics. The absence of other types, such as borrowing, reduplicatives, elliptic rhyming slang, reversed forms, back formation, infixes, and onomatopoeia, indicates selective linguistic choices by Drake. Overall, the study concluded that slang word in “God’s Plan” by Drake functions as a deliberate linguistic and sociocultural tool, enhancing expressiveness, stylistic effect, and audience engagement in contemporary hip-hop music.